Early environments drive diversity and floristic composition in Mediterranean old fields: Insights from a long-term experiment - Cayuela, Luis; Rey Benayas, Jose Maria; Maestre, Fernando T; Escudero, Adrián (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2008)
While many studies have explored how previous and current environmental conditions affect the performance of individual organisms, their relative importance as drivers of current diversity and composition of communities is virtually unknown. We evaluated the response of herbaceous communities to previous (experienced during early establishment) and current environmental conditions by comparing their composition and diversity in an abandoned Mediterranean cropland planted with Quercus ilex subsp. ballota L. seedlings. These seedlings received different experimental treatments (summer irrigation and artificial shading) during the first three years after planting, and were interrupted from then on. We tested two complementary hypotheses: (i) the previous environments experienced by the herbaceous communities during their establishment have a long-term carry-over effect on diversity and composition of species assemblages and (ii) these communities are influenced by their current environment, particularly by the woody layer and the soil conditions. Overall, we observed an important contribution of initial environmental conditions in determining the current diversity and composition of herbaceous communities. Amelioration of environmental conditions, particularly water stress, during community establishment resulted in a decrease in alpha and beta diversity, possibly as a consequence of decreasing environmental heterogeneity. Previous environments accounted for 26.3% of the explained variance in current community composition. Annuals, legumes and forbs also responded significantly to previous environments, which explained 27.9%, 36.2% and 30.1%, respectively, of the variance in their composition. Our results suggest that those species present at a particular site early in succession pre-empt the site and influence vegetation dynamics on that site for a long time. This study provides important insights for understanding the mechanisms underlying the ecological effects of issues like cropland reforestation and woody vegetation encroachment. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Ecological stability; Initial floristic composition; Vegetation dynamics; Woody vegetation cover

Early environments drive diversity and floristic composition in Mediterranean old fields: Insights from a long-term experiment - Cayuela, Luis; Rey Benayas, Jose Maria; Maestre, Fernando T.; Escudero, Adrián (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2008)
While many studies have explored how previous and current environmental conditions affect the performance of individual organisms, their relative importance as drivers of current diversity and composition of communities is virtually unknown. We evaluated the response of herbaceous communities to previous (experienced during early establishment) and current environmental conditions by comparing their composition and diversity in an abandoned Mediterranean cropland planted with Quercus ilex subsp. ballota L. seedlings. These seedlings received different experimental treatments (summer irrigation and artificial shading) during the first three years after planting, and were interrupted from then on. We tested two complementary hypotheses: (i) the previous environments experienced by the herbaceous communities during their establishment have a long-term carry-over effect on diversity and composition of species assemblages and (ii) these communities are influenced by their current environment, particularly by the woody layer and the soil conditions. Overall, we observed an important contribution of initial environmental conditions in determining the current diversity and composition of herbaceous communities. Amelioration of environmental conditions, particularly water stress, during community establishment resulted in a decrease in alpha and beta diversity, possibly as a consequence of decreasing environmental heterogeneity. Previous environments accounted for 26.3% of the explained variance in current community composition. Annuals, legumes and forbs also responded significantly to previous environments, which explained 27.9%, 36.2% and 30.1%, respectively, of the variance in their composition. Our results suggest that those species present at a particular site early in succession pre-empt the site and influence vegetation dynamics on that site for a long time. This study provides important insights for understanding the mechanisms underlying the ecological effects of issues like cropland reforestation and woody vegetation encroachment. (C) 2008 Elsevier Masson SAS. All rights reserved.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75015 PARIS, FRANCE publisher: GAUTHIER-VILLARS/EDITIONS ELSEVIER
Keywords: Ecological stability; Initial floristic composition; Vegetation dynamics; Woody vegetation cover

Mortalidad y crecimiento de plantones de quercus ilex en una tierra agrícola abandonada en toledo - Rey Benayas, Jose Maria (II Congreso Forestal Español, 1997)
Considerable quantities of agricultural land are being transformed into forested lands in E.U. countries. To assess afforestation practice, we analyzed the growth and mortality of 800 Quercus ilex' subsp. ball()ta seedlings in a set-aside agricultural land under semi-arid Mediterranean climate conditions in Toledo, Spain. The mortality and growth of the seedlings were monitored for three years after planting with an experimental design that included all four combinations of i) irrigation or no irrigation in the dry season and ii) artificial shading or no shading. Significant differences in mortality and growth (height, stem diameter and crown projected area) were found among treatments. Mortality was highest (47%) in the control plots, and very similar (around 7%) for the irrigation, shade, and combined treatments. Most of the mortality occurred after the first dry season. The low mortality in irrigated but not shaded plots in the first dry season is attributed to the protective role of a thick layer of the weed Amaranthus retroflexus L. Seedling growth was greatest on average under irrigation and shade conditions. Shade was found to have a significant effect for all growth measurements, while irrigation alone only affected stem diameter growth, and crown projected area in interaction with shade. We conclude that the reduction of summer stress must be considered in the early stages for successfull afforestation practices with oaks in set-aside agricultural lands of dry environments.
Keywords: Agriculturalland; Growth; irrigation; shade; Survival